Performance Assesment of the Implementation Green Supply Chain Management in the Micro Scale Food Industry Companies: Case Study of Black Grass Jelly Producer in Kediri - Lina Saptaria; Sudarmiatin Sudarmiatin; Agus Hermawan (International Journal of Social Service and Research, 2022)
The development of the concept of an environmentally friendly industry enriches the paradigm of industrial management worldwide. The result of application concept from Green Supply Chain Management (GSCM) in large-scale industries has been widely publised, while the result of application concept from GSCM in micro, small, and medium scale industries is insufficient. This study aims to explore the application of GSCM in the micro scale food industry, a case study in the black grass jelly manufacturing industry. In this study, GSCM performance assessment was carried out to find out how the company’s overall performance improved. The methods used in this research are Green Supply Chain Operation Reference (GSCOR) and Analytical Hierarchy Process (AHP). The survey questionnaire was developed based on literature studies and interviews with three industry players producing black grass jelly and distributed to 100 respondents. The findings propose 20 Key Performance Indicators (KPI) to measure GSCM performance in micro, small and medium scale food industry companies. The value of GSCM performance measured based on economic, operational, and environmental aspects can improve the company’s overall performance